STRENGTHENING DIVERSION REGULATIONS AGAINST CHILDREN DRUG ABUSE - Indra Retnowati (Universitas 17 Agustus 1945 Semarang, 2020)
Children are the nation's next-generation who must be protected from all forms of violence, discrimination and deprivation of liberty. The purpose of writing this article is to find out and analyze legal regulations in Indonesia, which seek to provide legal protection for children who abuse narcotics and how the sanctions can be imposed. The writing of this article uses the empirical normative juridical research method, which is a study that seeks to analyze a qualitative descriptive of events that are happening in the community, especially regarding the protection of children in conflict with the law. The results showed that children who dealt with narcotics abuse did not get diversion, such as the case in Court Decision Number 19/Pid.Sus-Anak/2019/PN.Smg, in which a fifteen-year-old child who uses Narcotics Category I is carrying one bag of a small plastic clip in the form of Methamphetamine and the urine turns out to be positive containing Methamphetamine is threatened with Article 114 paragraph (1) Juncto Article 132 paragraph (1) of Law Number 35 of 2009 concerning Narcotics with the threat of 5 (five) years imprisonment, this is contrary to the purpose of diversion as in Article 6 letter b of Law Number 11 of 2016 concerning the Criminal Justice System for Children which states, diversion aims to prevent children from being deprived of freedom. Children have the right to get their rights without asking for it. Based on Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, the child is sentenced to two years and work training for three months. Children should not be penalized and get Diversion.